Chromium and Chromium nitride thin films deposited by HiPIMS using short pulses - Ferrec, Axel; Schuster, Frédéric; Jouan, Pierre-Yves; Djouadi, Mohamed Abdou (International Conference on Plasma Surface Engineering, 2013)
The chromium nitride thin films are studied since several years and are widely use in mechanical applications as corrosion barrier. It has already been established that magnetron sputtering can improve by many ways the chromium nitride properties such as hardness, adhesion, oxidation resistance. A new development of this process, named HiPIMS (High Power Impulse Magnetron Sputtering), allows enhancing coating properties. In the first part, the objective of this study is to check the influence of the nitrogen content in the gas mixture on the CrN thin film (on the structure, the morphology). And next, the annealing treatment was investigated to study their behavior at high temperature.